The hypercalcaemia of CYP24A1 inactivation: new ways to improve diagnosis and treatment - Dusso, Adriana S. (Clin Kidney J, 2015)
This case report presents fluoconazole efficacy to reduce hypercalcaemia and increased urinary calcium excretion in a patient with nephrocalcinosis after a long history of recurrent renal stones caused by a loss-of-function mutation of the CYP24A1 gene. The CYP24A1 gene codes for a key enzyme in the vitamin D endocrine system that protects against vitamin D toxicity by degrading the circulating excess of both 1,25-dihydroxyvitamin D, the hormonal form of vitamin D, and its precursor, 25-hydroxyvitamin D. In order to expedite the identification of this rare disorder and improve therapies to avoid its progression to nephrocalcinosis, this editorial updates the current knowledge on the frequency of CYP24A1-inactivating mutations, the features of their early clinical presentation and progression, and the pathophysiology of vitamin D activation in health and in granulomatous disorders that may help improve current treatment.